Walking systems of robots - Didkivskiy, Oleg; Mishchuk, Dmytro (КНУБА, 2024)
Although wheeled vehicles dominate today, there is know that stepped locomotion systems have significant advantages on uneven surfaces. They use only a few points of contact with the surface for support, unlike wheeled or tracked machines that create continuous contact. In addition, walkers are significantly less disruptive to the soil, which can be important in certain areas. However, these advantages are accompany by the complexity of the design. A large number of degrees of freedom requires careful layout, the development of powerful drives and special mechanisms that reduce shock loads. The control system must not only process information about the environment, but also make decisions about movement and control their implementation. The main problem of walking robots lies in the development of a control system since the existing experience in creating complex automatic systems cannot be directly apply to control such devices. The creation of industrial robots capable of replacing humans in many areas of modern production, as well as automatic systems that can be used in conditions dangerous for humans, is an urgent scientific and technical problem. One of the important classes of robots are walking robots designed to move over difficult terrain.
Keywords: stepping systems; robots; review; robotics; 621.865.8